Facial aging - Andres, Rodney H. (2000)
Image warping and morphing has been around for decades, but has gained popularity only in recent years. The increasing popularity of this field of image processing was brought by its widespread application in entertainment - movies, commercials, music videos etc. The purpose of this project is to apply image warping and morphing techniques in a more serious field - facial aging. The idea is to take a digitized image of a human face and, employing warping and morphing techniques, produce a reliable image of what the face will look like in a user-specified number of years. In working toward this goal, research must be conducted on two main areas. The first area of research is on the biological aspect of the project. Here we will determine the precise changes all the parts of a human face (i.e eyes, nose, chin) undergo as we age. We will also deal with the problems of determining the minimum age of a person from which a prediction can be made, and identifying a range of years in which we can reliably age a human face. The second area of research is on the technical aspect of the project - on image analysis and processing, particularly in the fields of image warping and morphing. From the research so far, the Meshwarp Algorithm and Fields-Based Warping seem to be the promising algorithms to be used in the project. Algorithms on edge detection and image segmentation will also be needed.